Capital structure of enterprises as a factor of ensuring financial stability - Maryna Berest; İrina Zhuravlyova; Alyona Honcharenko (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
The aim of the study is todevelop a methodological approach to assess the impact on the financialstability of enterprises of the processes of formation and use of intellectualcapital in the structure of total capital. Systematic, monographic, analysis andsynthesis, induction and deduction, the method of financial ratios, clusteranalysis, regression analysis, factor analysis. The work is characterized bythe content and highlights the key factors of the concept of "financialstability of the enterprise." Using cluster analysis, groups ofmachine-building enterprises of the Kharkiv region were formed depending on thestructure and efficiency of capital use. A methodological approach has beencreated for empirical studies of the influence of intellectual capital on theresults of activities of machine-building enterprises of the Kharkiv region forthe selected clusters. It has been established that there is a positiverelationship between the processes of functioning of intellectual capital andthe financial results of enterprises; the impact of the efficiency of usingintellectual capital on asset turnover is not unidirectional, but thecontribution of the efficiency of using the components of intellectual capitalin obtaining these results differs for enterprise clusters; individualcomponents of intellectual capital without the presence of the rest are notsignificant. The factors of the influence of intellectual capital on theidentified clusters of engineering enterprises are identified, which will revealthe reserves of effective reproduction of intellectual capital on the selectedgroups of enterprises. Тhe practical significance of the results is that theiruse will allow enterprises reasonably structure in both total and intellectualcapital, increase the effective use of material, financial and intellectualcomponents. Methodical recommendations contained in the study, providing acomprehensive approach to management of capital structure formation andidentification of potential areas for optimization.